Membumikan Nilai-nilai Nasionalis-Pancasilais dalam Keluarga sebagai Implementasi Membangun Moderasi Bangsa - Juwono, Hendro (Sekolah Tinggi Islam Blambangan Banyuwangi, 2019)
Abstract: In the family there are sub-sections starting from father, mother, and child. Togetherness of children with parents before children continue their studies in the context of self-development is enough to determine the attitudes, views, and behavior in the future, because the position of the two parents to children is the first madrasa. Value is an ability that is believed to exist in an object that causes someone and group interest. Whereas according to Dayakisni value is a broad tendency to prefer or choose certain conditions compared to others. So grounding nationalist values ??is a form of planting values ??of lovers of the country and the nation, so that with this love someone will automatically search for all information about something he loves in order to protect and defend anyone who tries to disrupt and even undermine the integrity of his nation .